A novel chaotic image encryption technique based on multiple discrete dynamical maps - Khan, Majid; Masood, Fawad (Multimedia tools and applications, 2019)
The propagation of information over insecure communication system is one of the most important aspect of digitally advance era. The electronic information is travels in form of binary bits. The secrecy of these digital contents is one of the most important issue of existing world. In this article, we have utilized multiple chaotic iterative maps in order to propose a novel image encryption technique. The suggested encryption added confusion as well as diffusion in offered scheme which is one of the most fundamental aspect of encryption technique. We have tested our anticipated scheme against different performances analysis and compared it with already existing results. The designed scheme is capable of providing an excellent privacy to digital images.